“Here Comes the Teacher”: Navigating the Complexities of Being a Teacher in Rural Finland - Unn-Doris K. Bæck; Outi Autti (Education Sciences, 2025)
This study examines the complexities faced by teachers in rural Finland, focusing on tensions between professional roles and social lives within tight-knit communities. This research addresses the challenges of maintaining well-qualified teaching staff in rural schools. The purpose of the study is understanding the experiences of rural teachers and the challenges they face, including high visibility, community expectations, and blurred boundaries between personal and professional lives. The study uses a qualitative research design, employing in-depth interviews with 21 teachers across two rural locations in Northern Finland. The interviews focused on work experiences, roles, and reflections on the local educational context. The findings highlight that rural teachers experience a blurring of professional and social roles, leading to feelings of being constantly “on the job” and a lack of privacy. Community expectations often dictate their behavior outside of school. The study also reveals divisions within the teaching staff between local and commuting teachers. The study concludes that the cultural narrative of being a teacher in rural contexts includes traditional expectations of teachers, clashing with modern notions of teaching as a profession. The study emphasizes the importance of preparing teachers to be community-ready, acknowledging the challenges of rural teaching.